Dual-series 2 x 4 switched-beam nolen matrix for fifth generation wireless communication system - Mohd. Suhaimi, Nazleen Syahira (2018)
A new evolvement towards 5G technology requires a super high frequency to provide large channel capacity, low power consumption and low interference. Up to the present, the passive microwave devices with the super high frequency range are becoming necessity to be deployed due to the great features that are capable in representing significant advances in wireless communications. However, high interference occurs due to multiple signals coexisting in the super high frequency. Integration of switched-beam antenna that employs scanning of multi-beams with a proposed Nolen Matrix can be a solution to overcome this issue. The coupler with loaded T-shaped stubs, loaded stubs and Schiffman phase shifters as well as edge chamfered inset feeding microstrip patch array antenna are designed as the key components for the dual-series 2 x 4 switched-beam Nolen matrix. The loaded Tshaped stubs are introduced at each side of the microstrip lines nearby the square patch of the couplers to achieve various coupling values. All simulation results are obtained using Computer Simulation Technology software. The S-parameter measurement of the proposed couplers and dual-series 2 x 4 switched-beam Nolen matrix are performed using vector network analyzer, while its radiation pattern measurement is executed in an anechoic chamber. The amplitude and phase imbalances are ± 1 dB and 5° between 24.75 GHz and 27.25 GHz for the proposed couplers as well as between 25.75 GHz and 26.25 GHz for the phase shifters, respectively. Whereas, the respective amplitude and phase imbalances of 2 x 4 switched beam Nolen matrix are ± 3.5 dB and 10° across the designated frequency range of 25.75 GHz to 26.25 GHz. Meanwhile, at the center frequency of 26 GHz, the simulated and measured main beam directions are 10° and 12°, respectively when signal is fed at port 1, whereas -31° and -31.5°, respectively at port 2, with the highest measured gain of 10.19 dB and percentage of radiation efficiency of 59.98 %.